Facile construction of a 3D tumor model with multiple biomimetic characteristics using a micropatterned chip for large-scale chemotherapy investigation. Issue 9 (21st March 2023) - Sun, Meilin; Zhang, Jinwei; Fu, Wenzhu; Xuanyuan, Tingting; Liu, Wenming
Abstract : We present a simple, controllable, stable, and massive production of 3D tumors with dimensional-uniformity and multiple biomimetic characteristics using a micropatterned chip. Abstract : The establishment and application of biomimetic preclinical tumor models for generalizable and high-throughput antitumor screening play a promising role in drug discovery and cancer therapeutics. Herein, a facile and robust microengineering-assisted methodology for highly biomimetic three-dimensional (3D) tumor construction for dynamic and large-scale antitumor investigation is developed using micropatterned array chips. The high fidelity, simplicity, and stability of chip fabrication are guaranteed by improved polydimethylsiloxane (PDMS) microcontact printing. The employment of a PDMS-micropatterned chip permits microscale, simple, biocompatible, and reproducible cell localization with quantity uniformity and 3D tumor array formation with geometric homogeneity. Array-like 3D tumor models possessing complex multilayer cell arrangements, diverse phenotypic gradients, and biochemical gradients were prepared based on the use of easy-to-operate chips. The applicability of the established biomimetic models in temporal and massive investigations of tumor responses to antitumor chemotherapy is also verified experimentally. The results support the importance of the dimensional geometry and biomimetic degree of 3D tumors when conducting antitumor screening to explore drug susceptibility and resistance. This work provides a facile and reliable strategy to perform highly biomimetic tumor manipulation and analysis, which holds great potential for applications in oncology, pharmacology, precision medicine, and tissue microengineering.